Increasing the Ability to Listen to Fairy Tales Through the YouTube Kids Application for Class IV Students at UPT SDN 192 Barru - Magfirah, Rizqah; Ramadhan, A.Anugrah Sucilia; Nasharuddin, Nasharuddin (Jurnal Ilmiah Mandala Education (JIME), 2025)
his study aims to identify improvements in storytelling listening skills among fourth-grade students at SDN 192 Barru using the YouTube Kids application. The research is a Classroom Action Research (CAR), with procedures involving planning, action implementation, observation, and reflection.The results showed that the students’ storytelling listening skills improved across cycles. In Cycle I, the average score was 56, which increased to 88.2 in Cycle II. The learning mastery also improved, with only 8 students (33.33%) achieving mastery in Cycle I, compared to 21 students (82.5%) in Cycle II, fulfilling the classical mastery criteria. Additionally, the use of the YouTube Kids application encouraged more active student participation, as reflected in increased activity from Cycle I to Cycle II.